Relevance of drilling and blasting operations with direct cuts when carrying out horizontal rock and exploration excavations with influence of geological and structural features of the rock massif - Aleksey Nikolaevich Maslowsky; Viktor Grigoryevich Lukyanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance of the work is caused by necessity of economic and social development, providing operating companies with a source of raw materials. The drilling-and-blasting method is the most productive. This method is the basic and still the most perspective mode of collapse of strong, especially strong rocks, when carrying out mountain and prospecting and operational developments. There are many factors which influence the efficiency of drilling-and-blasting operations, the geological specification is the main one. Annually the rates of prospecting surveys increase. Therefore there is a requirement of increasing penetration speed. At this stage the increase of penetration speed is achieved by introduction of new equipment and technology. Mining exploration production in mining industry is carried out by the traditional cyclical technology using drilling and blasting method for separating rocks from the array. This technology has not undergone significant change over a long period. The total time required for hole drilling is in the range of 30…40 % and 50…60 % at ore deposit exploration within cycle time balance. Thus, for the last 10-20 years, no significant changes occurred in the time distribution. However, the absolute values of drilling duration decreased in 2-3 times because of application of more powerful drilling machines, mounting devices, improving work organization. The important and actual task is searching for new directions in increasing the efficiency, quality and profitability of drilling-and-blasting operations due to optimization of technological and technical indicators. The aim of the work is to develop and to select the technology of drilling-and-blasting operations with direct burn cuts applying geological structural features of the massif.